TINJAUAN TENTANG KEABSAHAN PERKAWINAN TANPA WALI NASAB MENURUT KOMPILASI HUKUM ISLAM (KHI) - Fitcanisa, Jenny Divia; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Provisions regarding marriage guardians are based on the provisions of each religion and the beliefs of those who carry out the marriage. This is in accordance with Article 2 Paragraph (1) of Law Number 1 of 1974 concerning Marriage which states that a marriage is legal if carried out according to the law of each religion and belief. Whereas in Islamic law, guardians in marriage are "harmonious" meaning they must be present in marriage, without a guardian, the marriage is considered invalid. Therefore, the validity of marriage in Islam is highly determined by the marriage guardian, with the provisions of articles 21 and 23 of the Compilation of Islamic Law (KHI).This type of research is sociological legal research. Sociological law research is research conducted directly on site or in the field to obtain data to provide a complete and clear picture of the problem under study, this research was conducted at the Office of Religious Affairs in Bukit Raya District, Pekanbaru City. From the results of this study there are two things that can be concluded. First is the validity of a marriage without guardian nasab according to the Compilation of Islamic Law (KHI). Second, the consequences arising from marriage without guardians nasab.Therefore, couples who do marriages that are not in accordance with Article 4, Article 21 and Article 23 then the marriage is invalid so that it causes legal consequences. The author's advice, first, couples who want to get married should pay more attention to the existing rules for the validity of the couple's marriage. Secondly, the KUA must also be more careful and provide information about the pillars and the terms and consequences that arise if the pillars and conditions are not met with the couple who want to get married so that not many more people do not know the terms and conditions of the marriage JOM Fakultas Hukum Universitas Riau Volume VII Nomor 2 Juli - Desember 2020Keywords: Guardian Nasab-Marriage-Compilation of Islamic Law